Evaluacion fitosanitaria y potencial de rendimiento de algodones de color em Lambayeque - Perú - Idrogo, Blanca Asteria Acuña (2009)
The present reseaech paper was made in the District,Province and Region Lambayeque located in northern Perú during the agricultura seasons: 2004-2005, 2005- 2007 and 2006-2007. The objetive was to evaluate the entomo fauna behavior and the This research work is run in the District, Province and Region Lambayeque, Peru during the crop season 2004-2005, 2005-2006 and 2006 - 2007 with the objective of evaluating the behavior of the entomofauna and yield potential native cotton (Gossypium barbadense L Ssp. Peruvianum).) cotton called "country". The crop was installed in June 2004 beginning with a nursery, in an area corresponding to Ferreñafe Sican Museum and its final installation in the field of Sipan Museum in Lambayeque, at an altitude of 29 meters, average temperature 22.5 º C, humidity on 75% and an average rainfall of 24 mm. 1.333 plants were installed. Also served to assess the ecotypes of color, material valued for its natural color, with a genetic resource of great value to work rescuing this poor germplasm, which is in danger of extisiòn due to the introduction of commercial hybrid , that would put in risk so precious ancestral legacy. We found significant genetic variation in all attributes evaluated. Ferreñafe province had the highest genetic variability in fiber color, the colored ecotypes present five out of nine. The most critical phases of pest attack were sprouting, fruiting and capsule opening. There was a low infestation of worm borer leaf Bucculatrix thurberiella, "Arrebiatadas" Dysdercus peruvianus "Peruvian beaked" Anthonomus vestitus and "wart mite" Acaliptus gossypii, mainly due to unsuitable conditions for their development. The native cotton crop will be greatly affected by the attack of pests if not done an adequate integrated pest management. The more promising ecotypes were: Orange-face, Fine red, white and pink White simple, 2903, 1880, 1642 and 1.24 kilos per plant, respectively. For weight of weed, highlights the ecotypes: Fine Colorado Claro Fifo 3.95 to 2.96 g, respectively, was found in the first harvest of the arboretum A , a greater number of fruit branches with 43,797 branches, with respect to the soca harvest, which formed only 10,643 fruit branches. In the arboretum "B", the results were the same trend. Sample sizes were adequate and representative of the population. The data had a normal or approximately normal distribution.